2019
DOI: 10.1016/j.microrel.2019.113489
|View full text |Cite
|
Sign up to set email alerts
|

Reliability comparison of AlGaN/GaN HEMTs with different carbon doping concentration

Abstract: The reliability of AlGaN/GaN HEMTs adopting Fe and C co-doping, with high and low carbon doping concentration was investigated by means of different stress tests. Firstly, DC and pulsed I-V characterization at room temperature are discussed, then drain step stress tests at different gate voltages are compared, afterwards, the constant stress at different bias points are discussed. Results show that the high C HEMTs showed reduced DIBL, smaller leakage current, as well as decreased electric field, leading to an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…DC characteristics showed that the "Fe Reference" devices have the smallest leakage current; and the "Fe + High C" device has reduced Drain Induced Barrier Lowering (DIBL) effects due to the better charge confinement due to the high carbon doping concentration, as shown in [8]. The EL intensity follows a bell shape versus VGS biasing for all devices, as shown in Fig.…”
Section: Preliminary Resultsmentioning
confidence: 77%
See 3 more Smart Citations
“…DC characteristics showed that the "Fe Reference" devices have the smallest leakage current; and the "Fe + High C" device has reduced Drain Induced Barrier Lowering (DIBL) effects due to the better charge confinement due to the high carbon doping concentration, as shown in [8]. The EL intensity follows a bell shape versus VGS biasing for all devices, as shown in Fig.…”
Section: Preliminary Resultsmentioning
confidence: 77%
“…The demand for industrial-level 0.15 m HEMTs for low-noise and power amplifiers up to and beyond 50 GHz [5] has been enhanced by 5G and radar applications. In order to control short-channel effects, which directly determine leakage current and RF reliability [6], various approaches have been used, including back-barriers [7], C or C+Fe co-doping [8], N-polar GaN/AlGaN channels [9] and so on. Reliability is another key issue that has to be taken into consideration during the improvement of HEMT technologies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be noted, however, that short-term reliability, in particular for what concerns hot-electron effects, also depends on the interplay between charge trapping and electric field distribution. In [80], we compared the on-wafer reliability of 0.15-µm GaN HEMTs for microwave applications adopting Fe and C co-doping, with the same Fe doping profile, but different levels of C doping within the GaN buffer. At increasing C content, short-channel effects were reduced, at the expense of a slightly higher CC, related to the presence of C N acceptors.…”
Section: Deep Levels Related To Carbon Dopingmentioning
confidence: 99%